2005
DOI: 10.1007/s10350-004-0901-8
|View full text |Cite
|
Sign up to set email alerts
|

Topical 5-Fluorouracil in the Management of Extensive Anal Bowen's Disease: A Preferred Approach

Abstract: Topical 5 percent 5-fluorouacil therapy is a safe and effective method to treat anal Bowen's disease. Wide local excision is appropriate for smaller, isolated areas of disease. Anal Bowen's disease was not associated with colonic or other neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
(34 reference statements)
0
32
0
2
Order By: Relevance
“…A survey of the American Society of Colon and Surgeons members revealed that local excision is the preferred treatment for the majority of patients with perianal Bowen's disease [9]. There are numerous reports in the literature supporting that such approach is safe [9,10,12,13,26,27]. However, the inability to permanently eradicate the disease due to the persistence of HPV remains one of the biggest challenges of treating neoplastic anal lesions, especially in immunocompromised individuals [10,11,25,26,30].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A survey of the American Society of Colon and Surgeons members revealed that local excision is the preferred treatment for the majority of patients with perianal Bowen's disease [9]. There are numerous reports in the literature supporting that such approach is safe [9,10,12,13,26,27]. However, the inability to permanently eradicate the disease due to the persistence of HPV remains one of the biggest challenges of treating neoplastic anal lesions, especially in immunocompromised individuals [10,11,25,26,30].…”
Section: Discussionmentioning
confidence: 98%
“…However, there is little guidance as to the optimal management of Buschke-Löwenstein tumor because of its rarity [4][5][6][7][13][14][15][16][17][18][19][20][21][22]. Furthermore, the management of AIN is evolving without widely accepted standard of care [1,[8][9][10][11][12][13][23][24][25][26][27][28][29][30][31]. Buschke-Löwenstein tumor was initially described as a neoplasm of the penis in 1925 and later reported in the anal area [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations